What do acquisition activities really cost? A case study in Estonian university libraries. Issue 6 (10th August 2015) - Kont, Kate-Riin
Abstract : Purpose: – The purpose of this paper is to mainly find out how well is time-driven activity-based costing (TDABC) suits for a university library setting in Estonia. For this purpose, all activities related to acquisitions process were identified and recorded in detail, and the cost of all these activities related to acquisition process in Estonian university libraries based on the example of the TDABC method were anlyzed. Design/methodology/approach: – The data used in this paper is based on a review of relevant literature to provide an overview of the concept of the different cost accounting methods suitable for the measurement of the acquisition process. Through a case study, conducted among Estonian university libraries, the TDABC approach was used to analyze the acquisition process in university libraries. More specifically, the acquisition process studied concerned print format books, audiovisual documents and sheet music, and covered acquisition processes such as receipt of orders, ordering documents, communication with bookshop (if necessary), receiving documents and communication with the customer. Findings: – On the basis of the current study it can be said the TDABC methodology seems to be one of the best tools for understanding cost behavior and for refining a cost system for university libraries. While analyzing the results, it appeared that the difference in time and cost for acquiring a document can be remarkable and concerns both – acquiring foreign documents (documents from other countries) and acquiring domestic documents, and between the university libraries chosen for the current study. Originality/value: – The subject of cost accounting as a performance measurement method is in general an unexplored field in Estonian university libraries. Time guidelines for acquiring the documents were, however, quite common in the 1980s in the USSR, including Estonia. Soviet-wide regulatory documents were issued on all library work processes, but each library could still implement their own rules. In the 1990s, the regulations were consigned to oblivion. Very few cost surveys involving different library activities have been carried out in Estonia and none have been published. Where such studies have been conducted, the results remain for internal use only.